Histopathological Spectrum and Clinical Correlation of Gastrointestinal Mucosal Biopsies in Patients with Chronic Diarrhea. A Cross-Sectional Study - Sheema Khan, Muhammad Zubair, Muhammad Adnan Masood, Ahmad Jawad Awan, Saim Sattar, Aisha Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic diarrhea, defined as diarrhea lasting four weeks or more, is a common clinical problem with a wide range of etiologies. Its causes may include infectious, inflammatory, autoimmune, and neoplastic conditions. While clinical assessment and laboratory investigations provide useful insights, histopathological evaluation of gastrointestinal mucosal biopsies remains the gold standard for accurate diagnosis and management. Objective: To determine the histopathological spectrum of gastrointestinal mucosal biopsies in patients with chronic diarrhea and to correlate these findings with clinical features. Methods: This cross-sectional study was conducted in the Department of Pathology in collaboration with the Department of Gastroenterology, Khyber Teaching Hospital, Peshawar, Pakistan, from January 2022 to July 2023. A total of 100 patients with diarrhea persisting for more than four weeks were included. Endoscopic biopsies were obtained and processed using hematoxylin and eosin staining. Special stains were employed when required. Clinical features were recorded, and correlation with histopathological findings was analyzed using SPSS version 25. Results: The mean age of patients was 39.2 ± 13.1 years, with a male predominance (55%). The most common presenting symptom was watery diarrhea (62%), followed by weight loss (48%) and abdominal pain (40%). Histopathology revealed inflammatory bowel disease in 28% of cases, chronic nonspecific colitis in 22%, infectious colitis in 15%, celiac disease in 12%, microscopic colitis in 8%, and neoplastic lesions in 7%. Significant clinicopathological correlations were observed, particularly in cases of IBD (p=0.01) and celiac disease (p=0.02). Conclusion: Histopathological examination of gastrointestinal mucosal biopsies provides invaluable diagnostic information in patients with chronic diarrhea. Routine biopsy is recommended in all such patients to differentiate overlapping conditions, ensure accurate diagnosis, and guide effective treatment strategies. Keywords: Chronic diarrhea, gastrointestinal mucosa, histopathology, inflammatory bowel disease, celiac disease, colitis.